Perencanaan Keuangan untuk Santri dan Pemula : Pengabdian - Gazali, Masfar; Suparyati, Agustina; A. Tribudi, Debbie; Parinduri, Aina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Good financial management for students and individuals is crucial for their future survival. Individuals need financial management. To prepare for independent living, students must learn how to manage money, from budgeting to saving. The problem is, not all participants understand and comprehend how to manage their finances effectively due to a lack of financial literacy. Financial training programs not only provide technical knowledge but also increase financial awareness and literacy. Students learn to recognize the value of money and use it appropriately, so they are better prepared for the real world after graduation. The goal of financial management is to understand how to manage income and expenses. Good management prevents reckless spending and allows for savings and investments. Furthermore, the goal of managing finances fosters discipline in recording income and expenses for future use. The results of this training show that 90% of students understand how to manage their finances effectively.